Pajak Pintar untuk UMKM: Perencanaan Pajak bagi UMKM Siap Bersaing: Pengabdian - Kahfi Fikrianoor; Arifatun Nasihah; Ikhsan; Reza Saputra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service Program (PKM) was implemented to increase tax awareness and business legality among MSME brick factory operators in the Cilegon and Serang areas of Banten. The planning stage began with a field survey to identify the main problems faced by partners, namely a low understanding of tax obligations, minimal ownership of Taxpayer Identification Numbers (NPWP), and a negative perception that taxes are an additional burden. Based on these findings, the team developed an educational strategy using a social approach and norm theory, which emphasized a collective change in perception that tax compliance is a form of business professionalism. The organizational stage involved the formation of a PKM team consisting of lecturers and students. Lecturers played a role in developing materials and training, while students assisted participants in technical processes such as online NPWP registration. In the implementation stage, activities were carried out in the form of tax education workshops, online NPWP registration simulations. This approach was designed so that the education was not only informative but also built social awareness and collective motivation to become compliant taxpayers. Success indicators include a minimum 25% increase in understanding, an increase in NPWP registrations, and the formation of a communication network between MSME actors and tax agencies. Through these stages, the PKM activity is expected to create brick factory MSMEs that are more tax-aware, administratively orderly, and contribute to regional development. Collaboration between academics and the government is key to building a sustainable culture of tax compliance in the micro and medium enterprise sector.